PENERAPAN METODE BLENDED LEARNING PADA PERKULIAHAN DI PRODI PAI PTKIN - Mashuri; Mawardi; Ariska; Mashuri, Mashuri; Mawardi, Mawardi; Ariska, Ariska (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Blended Learning is a learning model that combines face-to-face (offline) and online learning as an effort to improve the quality of higher education. This method strongly supports the implementation of the Tri Dharma of Higher Education, aligns with the concept of Independent Learning, Independent Campus (MBKM), and is relevant to the characteristics of the technology-savvy millennial generation. However, its application is still limited to specific situations, and has not been well-planned and optimized for improving the quality of higher education. This study aims to describe the application of the blended learning method in Islamic Religious Education (PAI) learning at PTKIN. The research method used is a qualitative descriptive approach, which aims to describe a phenomenon as it is. The results show that the implementation of the blended learning method in PTKIN, specifically at IAIN Takengon and UIN Ar-Raniry Banda Aceh as the objects of this study, has not been systematic and sustainable, because it is still situational and not yet part of academic policy. The main challenges in implementation include technological aspects, such as limited network and learning facilities; pedagogical, such as low student interaction and participation; and psychological, such as boredom and decreased motivation to learn. To address these issues, various efforts have been implemented, including optimizing online resources, digital training, using platforms like Zoom and Google Classroom, implementing interactive learning methods, and improving student communication and motivation. In general, the implementation of blended learning at PTKIN Aceh has great potential for development, but requires policy support, increased digital capacity, and pedagogical innovation to ensure its effective and sustainable implementation.